Regulatory T cells inhibit autoantigen-specific CD4+ T cell responses in lupus-prone NZB/W F1 mice - Rosenberger, Stefan; Undeutsch, Reinmar; Akbarzadeh, Reza; Ohmes, Justus; Enghard, Philipp; Riemekasten, Gabriela; Humrich, Jens Y. (Frontiers in Immunology, 2023)
Introduction Progressive loss of regulatory T cell (Treg)-mediated control over autoreactive effector T cells contributes to the development of systemic lupus erythematosus (SLE). Accordingly, we hypothesized that Treg may also have the capacity to suppress the activation of autoreactive CD4+ T cells that are considered to drive autoimmunity. Methods To investigate whether Treg are involved in the control of autoreactive CD4+ T cells, we depleted CD25+ Treg cells either in vivo or in vitro, or combined both approaches before antigen-specific stimulation with the SLE-associated autoantigen SmD1(83-119) in the NZB/W F1 mouse model either after immunization against SmD1(83-119) or during spontaneous disease development. Frequencies of autoantigen-specific CD4+ T cells were determined by flow cytometry using the activation marker CD154. Results Both in vitro and in vivo depletion of CD25+ Treg, respectively, increased the frequencies of detectable autoantigen-specific CD4+ T cells by approximately 50%. Notably, the combined in vivo and in vitro depletion of CD25+ Treg led almost to a doubling in their frequencies. Frequencies of autoantigen-specific CD4+ T cells were found to be lower in immunized haploidentical non-autoimmune strains and increased frequencies were detectable in unmanipulated NZB/W F1 mice with active disease. In vitro re-addition of CD25+ Treg after Treg depletion restored suppression of autoantigen-specific CD4+ T cell activation. Discussion These results suggest that the activation and expansion of autoantigen-specific CD4+ T cells are partly controlled by Treg in murine lupus. Depletion of Treg therefore can be a useful approach to increase the detectability of autoantigen-specific CD4+ T cells allowing their detailed characterization including lineage determination and epitope mapping and their sufficient ex vivo isolation for cell culture.